Tinnitus Suppression by Low-Rate Electric Stimulation and Its Electrophysiological Mechanisms - Zeng, Fan-Gang (2011)
Tinnitus is a phantom sensation of sound in the absence of external stimulation. However, external stimulation, particularly electric stimulation via a cochlear implant, has been shown to suppress tinnitus. Different from traditional methods of delivering speech sounds or high-rate (>2,000 Hz) stimulation, the present study found a unique unilaterally-deafened cochlear implant subject whose tinnitus was completely suppressed by a low-rate (<100 Hz) stimulus, delivered at a level softer than tinnitus to the apical part of the cochlea. Taking advantage of this novel finding, the present study compared both event-related and spontaneous cortical activities in the same subject between the tinnitus-present and tinnitus-suppressed states. Compared with the results obtained in the tinnitus-presentstate, the low-rate stimulus reduced cortical N100 potentials while increasing the spontaneous alpha power in the auditory cortex. These results are consistent with previous neurophysiological studies employing subjects with and without tinnitus and shed light on both tinnitus mechanism and treatment.